HTML5 and CSS3 all-in-one for dummies - Harris, Andrew, 1964- (--For dummies., 2014)
This edition teaches you the fundamentals of HTML5 and CSS3, and then presents ways for using them with JavaScript, MySQL, and Ajax to create websites that work. It covers using JavaScript, PHP, MySQL, and Ajax in the context of programming dynamic Web pages with CSS3 and HTML5; includes self-contained minibooks that review HTML, CSS, design and layout, client-side JavaScript, Ajax and server-side, and putting it all together; examines new Web development advancements including new technologies and changes to the standards; and features a website that contains supporting materials including code and several valuable programs that are useful for Web development. This guide serves as the perfect reference for both Web development beginners and seasoned professionals looking to learn more about how to get the most out of the powerful combination of HTML5 and CSS3. --